Clinical profiles and trends in CD4+ counts to first-line antiretroviral therapy among HIV/AIDS patients in western part of Odisha state of India - B., Pradhan; C., Majhi; B., Murmu (International Journal of Research in Medical Sciences, 2018)
Background: HIV infection is globally pandemic and about 36.7 million people living with HIV/ AIDS (PLHA) in 2016. At present CD4+ count is the gold standard of immunological marker of disease severity. Highly active antiretroviral therapy (HAART) is the first line of treatment to improve CD4 count. AIMS AND OBJECTIVES of study was to observe the clinical profiles and response in CD4+ counts to first-line HAART in PLHA and their adverse reactions. Methods: Total 153 PLHA with CD4+ counts <250/µl was consecutively taken in the study and detail clinical examinations, baseline CD4+ counts and body weights were noted. HAART was started in 26 (16.99%), 37 (24.18%), 78 (50.98%) and 12 (7.84%) cases in WHO clinical stages of I, II, III, and V respectively and CD4+ counts, body weight and any adverse drug reactions were noted at 15 days, 3, 6, 18 and 24 months intervals and data were collected and analyzed. Results: Out of 153 cases 89 were male and 64 were female. Mean age was 35.4±9.08 years for male and 30.2±5.75 years for female. Mean baseline CD4+ count was 202±75/µl and mean body weight was 47.44kg. Mean CD4+ count was increased to 314.22±166.53, 343±194.02, 378±221.30 and 299.6±146.55/µl at 6, 12, 18 and 24 months respectively. Commonest adverse drug reaction was headache and GIT side effects. Conclusions: HAART improves clinical and immunological parameter CD4+ count in PLHA, irrespective of their clinical stages. Headache and GIT manifestations are commonest adverse drug reactions.